Correlation of Iron Status between Pregnant Women and their Corresponding Newborns - Humera Siddique, Muhammad Ayyub, Mansoor Nadeem (Journal of Rawalpindi Medical College, 2013)
Background: To determine correlation of iron status between pregnant women and their corresponding newborns using a combination of hematological and biochemical parameters. Methods: In this cross-sectional study venous blood samples from fifty pregnant women, with single fetus at term 37-42 weeks of gestation, having uneventful vaginal casearation section delivery, and their corresponding umbilical cord samples were obtained. C-reactive protein, blood complete picture, serum iron, serum ferritin, serum total iron binding capacity and serum transferrin saturation were performed. Pregnant women were divided into non-iron deficient, iron deficient and anemic with iron deficiency. Newborns with and without maternal anemia were placed in separate groups. Statistical analysis included descriptive analysis, Pearson’s correlation coefficient and one way ANOVA. Results: Among pregnant women, twenty two percent were iron deficient but without anemia and forty six percent were anemic (forty percent iron deficient and six percent non-iron deficient). Significant difference was observed in the mean values of hemoglobin and hematocrit between newborns with and without maternal anemia (p < 0.01). Significant association was observed between newborn and maternal iron parameters (p < 0.01). Conclusion: Iron related parameters are correlated between pregnant women and their corresponding newborns meaning that iron is transported from mother to fetus in direct proportion with the levels found in the maternal circulation.